Pengaruh Core Stability Exercise Terhadap Kelincahan Pada Pemain Futsal - , Fikry, Isnaini Herawati, SSt. FT, M. Sc (2017)
ABSTRACT STUDY PROGRAM S1 PHYSIOTHERAPY FACULTY OF HEALTH SCIENCE UNIVERSITY MUHAMMADIYAH OF SURAKARTA THESIS, 30 DESEMBER 2016 FIKRY/J120120045 "CORE STABILITY EFFECT OF EXERCISE ON PLAYERS AGAINST AGILITY FUTSAL" (Guided By Isnaini Herawati, S.ST.Ft., M.Sc,) Background:Futsal is a sport that requires agility/agility in a narrow space and time is short. Increased agility athlete can be done by providing Core Stability Exercise is necessary to increase the factors that affect the agility such as flexibility, strenght, power, speed, balance, and coordination. Objective: To determine of Core stability exercises to increase agility on a futsal player. Methods:This study is a quasi experimental design with Pre and Post Test with Control Group Design. The study population was all the players belong Hattrick futsal club Pabelan numbering as many as 16 people. The research sample as many as 15 people were divided into two groups: 8 as the experimental group was given core stability exercise regularly three times a week for 4 weeks and 7 as the control group was not given exercise. Agility research data collection using T-Test. Research data analysis using the Wilcoxon Signed Rank Test and Mann Whitney Test. Results: There was an effect on agility Core Stability Exercise on futsal players after statistical test using Wilcoxon test p-value 0.012 obtained in the treatment group and the control and there is a different effect after using statistical test Mann Whitney test was obtained p-value of 0.001. Conclusion: of the study is the level of agility initial (pre-test) in both groups are predominantly poor, the level of agility after the intervention (post-test) in the treatment group are mostly excellent, whereas in the control group most are poor, and the results of Wilcoxon Signed Rank Test and Mann Whitney test conclusion there is the effect of Core Stability Exercise to increase agility futsal players. Keywords: futsal, agility, core stability exercise